TEACHING LANGUAGES THROUGH TASKS IN A COMMUNICATIVE WAY (Лучшие интеллектуальные исследования, 2025)
Abstract: Task-Based Language Teaching (TBLT) has emerged as a powerful methodological approach within the field of second language acquisition. Rooted in communicative language teaching principles, TBLT emphasizes the use of authentic tasks as central units of planning and instruction. This article explores the theoretical foundation, key characteristics, pedagogical benefits, and practical challenges of implementing TBLT in classroom settings. It also provides critical reflections on how TBLT contributes to learner-centered education by promoting fluency, accuracy, and interaction. The discussion integrates empirical research findings and theoretical perspectives to offer a comprehensive view of TBLT's methodological significance.